AN INSTRUCTIONAL WRITING DESIGN IN TEFL - Masrul Masrul (Journal of English Language and Education, 2016)
This research discusses the elements of instructional design in model writing. In this model present guidelines for writing instructional design and technical elements in models writing. Instructional design models provide for a systematic approach of implementing the instructional design process for a specific educational initiative. The instrument is observation and test. The instructional models are followed by process of selected models of the Dick and Carey systems approach and description for each model will serve as the foundation and supporting points required for comparing and contrasting process of the models. The result is find some element that is Conduct instructional analysis, Analyze learners and contexts, Write performance objectives, Develop assessment instruments, Develop instructional strategies.